2008
DOI: 10.1111/j.1741-6787.2008.00126.x
|View full text |Cite
|
Sign up to set email alerts
|

The Evidence‐Based Practice Beliefs and Implementation Scales: Psychometric Properties of Two New Instruments

Abstract: In this study, initial evidence was provided to support the reliability and validity of the EBP Beliefs and Implementation Scales in a heterogeneous sample of practicing nurses. EVIDENCE TO ACTION: Use of the scales in future research could generate evidence to guide EBP implementation strategies in practice and education. Results could establish the extent to which EBP is being implemented and its effect on clinician satisfaction and patient outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

29
405
4
30

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 298 publications
(468 citation statements)
references
References 37 publications
(56 reference statements)
29
405
4
30
Order By: Relevance
“…(18) report low levels of nurses' responsibility for implementing an evidence-based nursing approach. Melnyk et al (10) found a statistically significant correlation between the implementation of an evidence-based nursing approach and the level of nurses' education and their ability to assume responsibility at the workplace. Nursing must respond to the changing needs of healthy and ill populations -nurses' professional training programmes must be adapted, with nursing itself becoming a graduate profession (bachelor's degree as the basic level of education).…”
Section: Discussionmentioning
confidence: 99%
“…(18) report low levels of nurses' responsibility for implementing an evidence-based nursing approach. Melnyk et al (10) found a statistically significant correlation between the implementation of an evidence-based nursing approach and the level of nurses' education and their ability to assume responsibility at the workplace. Nursing must respond to the changing needs of healthy and ill populations -nurses' professional training programmes must be adapted, with nursing itself becoming a graduate profession (bachelor's degree as the basic level of education).…”
Section: Discussionmentioning
confidence: 99%
“…Nurses' beliefs, skills, and knowledge related to EBP have an impact on the use of evidence in practice [8]. Strong beliefs in the value of EBP and positive attitudes toward it are associated with nurses' use of evidence in practice and are seen as important mediators in changing behavior related to EBP [9]. Given the influence of practitioners' beliefs on the successful implementation of EBP, a first step in its implementation may be to assess the nursing staff's beliefs regarding this approach.…”
Section: Introductionmentioning
confidence: 99%
“…[9] Other instruments were either not comprehensive enough or did not include the three topic domains of interest. For example, the belief and implementation scales by Melnyk et al [5] include knowledge questions, but do not dedicate a separate scale for assessing knowledge. Therefore, the aim of this study was to develop a concise and valid measure to assess nurse's value, knowledge and implementation of EBP.…”
Section: Introductionmentioning
confidence: 99%
“…[2] Despite wide acceptance as a gold standard to providing safe and high quality patient care, it is estimated that only a small percentage of nurses implement EBP on a consistent basis. [5] A lack of understanding of EBP and how evidence is integrated into practice has resulted in poor participation by nurses. [6] Consequently, evidence-based practice education has become a critical part of academic curricula and ongoing education programs for nurses with foci on the value of EBP * Correspondence: Fiona Paul; Email: Fiona.paul@childrens.harvard.edu; Address: Boston Children's Hospital, Boston, MA, United States.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation